The Assimilation of Young Workers into the Labour Market in France: A Stochastic Earnings Frontier Approach - Stephen Bazen; Khalid Maman Waziri (Institute of Labor Economics (IZA), 2017)
Stochastic earnings frontiers have been used in a relatively small number of papers to analyse workers' ability to capture their full potential earnings in labour markets where there is inefficient job matching (due to lack of information, discrimination, over-education or during process of assimilation of migrants). Using a representative survey of young persons having left full-time education in France in 1998 and interviewed in 2001 and 2005, this paper examines the process of their assimilation into normal employment and the extent to which job matches are inefficient in the sense that the pay in a job is below an individual's potential earnings (determined by education, other forms of training and labour market experience). Our results suggest that young workers manage to obtain on average about 82% of their potential earnings three years after leaving full-time education and earnings inefficiency had disappeared four years later. The results are robust to the treatment of selectivity arising from the exclusion of the unemployed in the estimation of the frontier.
Keywords: J30; J13; J24; C24; 330; stochastic earnings frontier; job matching; youth employment; earnings determination; sample selection stochastic frontier